Envisioning a Twenty-First Century Legal Education - W. Warren H. Binford (Washington University Journal of Law & Policy, 2014)
Imagine a law school in which you are taught only what you need to know, when you need to know it, using the teaching methods and resources best suited for you. Imagine a law school in which you are taught by the best scholars and lawyers in the world without ever leaving your campus. Imagine a law school that allows you to go almost anywhere around the globe to gain the experience you need and to develop the relationships that would best support your professional aspirations. Imagine a law school where professors are coaches, classmates are colleagues, and time and space are transcended. If you can imagine these things, you can envision the potential of digital technology to transform legal education in the twenty-first century. This Essay briefly considers the impact of digital technologies on legal education in the twenty-first century, such as adaptive learning software, digital assessments of learning outcomes, open courseware, video capture, simulated role plays, educational gaming, customizable digital textbooks, online courses, video- and online conferencing, social networking, online communities, and digital scholarship. It also recognizes the increasing engagement of digital educational resources in higher education generally, as well as by other professional education programs such as business schools, medical schools, and schools of education at universities including Harvard University, University of Pennsylvania, Northwestern University, and Stanford University. The Essay concludes that the emerging omnipresence of digital technologies in legal education is inescapable. Thus, legal educators must provide leadership and vision, partnering with publishers and software programmers and developers to ensure our students receive the best legal education possible in the Digital Age. If we do not, commercial enterprises will simply dictate our teaching resources and methods and, in the process, perhaps our obsolescence.
Keywords: legal education; legal education reform; future of legal education